Interfacial concentrations of chloride and bromide and selectivity for ion exchange in vesicles prepared with dioctadecyldimethylammonium halides, lipids, and their mixtures - Scarpa, Maria V. [UNESP]; Maximiano, Flavio A.; Chaimovich, Hernan; Cuccovia, Iolanda M. (American Chemical Society (ACS), 2002)
The local concentrations of chloride, Cl b, and bromide, Br b, in the interface of vesicles prepared with dioctadecyldimethylammonium chloride, DODAC, or bromide, DODAB, dipalmitoylphosphatidylcholine, DPPC, dimyristoylphosphatidylcholine, DMPC, and mixtures of DMPC, DPPC, and DODAC were determined by chemical trapping by analyzing product yields from spontaneous dediazoniation of vesicle-bound 2,6-dimethyl-4-hexadecylbenzenediazonium ion. The values of Cl b and Br b in DODAC and DODAB vesicles increase with vesicle size, in agreement with previous data showing that counterion dissociation decreases with vesicle size. Addition of tetramethylammonium chloride displaces bromide from the DODAB vesicular interface. The value for the selectivity constant for Br/Cl exchange at the DODAB vesicular interface obtained by chemical trapping was ∼2.0, well within values obtained for comparable amphiphiles. In vesicles of DPPC the values of Cl b were very sensitive to the nature of the cation and decreased in the order Ca 2+ > Mg 2+ > Li + > Na + > K + = Cs + = Rb + ≥ +. The effect of the cation becomes more important as temperature increases above the phase transition temperature, T m, of the lipid. The values of Cl b increased sigmoidally with the mol % of DODAC in vesicles prepared with DODAC/lipid mixtures. In sonicated vesicles prepared with DODAC and DMPC (or DPPC), the values of Cl b reach local concentrations measured for the pure amphiphile at 80 mol % DODAC. These results represent the first extensive study of local concentration of ions determined directly by chemical trapping in vesicles prepared with lipids, synthetic ampliiphiles, and their mixtures.
Keywords: Amphiphiles; Chemical trapping; Bromine compounds; Chlorine compounds; Dissociation; Ion exchange; Lipids; Mixtures; Phase transitions; Thermal effects; Surface chemistry